(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2008)
The article deals with the deetimologization as a semantic process, which modifies the base of lexical meaning and thus influences the word morpheme structure. The ancient forms are reconstructed by comparison of historically related units, those changes are analyzed which are embodied in the appropriate words during their functioning in language, and also primary wordformation connections are defined.